HYPOGLYCEMIC ACTIVITY OF SOME INDONESIAN RICE VARIETIES AND THEIR PHYSICOCHEMICAL PROPERTIES - Sri Widowati; Made Astawan; Deddy Muchtadi; Tutik Wresdiyati (Indonesian Journal of Agricultural Science, 2006)
Diabetes mellitus is a spectrum of inherited and acquired disorders characterized by elevating blood glucose levels. Diabetes is an abnormal carbohydrate metabolism, therefore, diet therapy for diabetics plays a key role in the management of the disease. Most Indonesian people consume rice as source of energy and protein. Generally, diabetics consume very limited rice because they believe that rice is the one of hyperglycemic food, even though different rice varieties have large range of glycemic index. The study aimed to evaluate hypoglycemic properties by using rat assay and chemical characteristics of 10 Indonesian rice varieties, i.e. Pandan Wangi, Rojolele, Bengawan Solo, Cenana Bali, Memberamo, Celebes, Ciherang, Batang Piaman, Cisokan, and Lusi. Taj Mahal, an herbal ponni imported rice, was used as a comparison. Male Sprague Dawley rats (150- 200 g body weight) were used for hypoglycemic assay. The rats were fasted overnight before the blood glucose was measured in the morning. The rats were then feed with 4.5 g rice per kg body weight by oral administration, followed by 1 ml of 10% glucose solution in the next 30 minutes. The blood glucose was measured for the next 30, 60, 90, and 120 minutes. Changes in blood glucose concentrations (mg dl-1) before and after the oral administrations were calculated for each rice variety tested. Results showed that Cisokan and Batang Piaman were categorized as low glycemic responses and Ciherang as high glycemic response, while the other varieties (Memberamo, Cenana Bali, Lusi, Bengawan Solo, Pandan Wangi, Celebes, and Rojo Lele) showed moderate glycemic responses. As the best hypoglycemic activity, Cisokan contained high amylose (27.6%), fat (0.87%), total dietary fiber (6.24%), resistant starch (2.02%), and lowest starch digestibility (52.2%), which are ideal for diabetic’s consumption. Ciherang as the worst hypoglycemic activity had low resistant starch (1.78%), low total dietary fiber (4.52%), and medium amylose (23.0%). This study implies that Cisokan variety is suitable for diabetic’s consumption.